2014
DOI: 10.1002/ppul.23144
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of a low single dose inhaled steroid against exercise induced bronchoconstriction

Abstract: A low single dose ICS offers acute protection against EIB in the majority of asthmatic children not currently treated with inhaled corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…[26][27][28][29][30] This single-dose effect showed a variability similar to the variability observed in longterm treatment. 30 We, therefore, hypothesized that the individual single dose response to ICS could function as a non-invasive predictor for the individual effectiveness of ICS treatment after 4-week treatment. This could be helpful to personalize treatment and prevent inappropriate long-term therapy and/or escalation of therapy.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…[26][27][28][29][30] This single-dose effect showed a variability similar to the variability observed in longterm treatment. 30 We, therefore, hypothesized that the individual single dose response to ICS could function as a non-invasive predictor for the individual effectiveness of ICS treatment after 4-week treatment. This could be helpful to personalize treatment and prevent inappropriate long-term therapy and/or escalation of therapy.…”
Section: Introductionsupporting
confidence: 60%
“…Previous studies demonstrated a significant acute effect of a single (high and low) dose ICS on bronchial responsiveness measured by an indirect bronchial provocation test 26‐30 . This single‐dose effect showed a variability similar to the variability observed in long‐term treatment 30 .…”
Section: Introductionmentioning
confidence: 60%
“…The magnitude of the effect was similar compared to previous studies with a high single dose of ICS. The protective effect against EIB of a low dose BDP inhaled in the standard posture is recently published by our study group [20].…”
Section: Discussionmentioning
confidence: 92%
“…Besides these chronic effects, previous studies have also shown acute protection against EIB after administration of only a single dose of ICS (43)(44)(45)(46). Visser et al demonstrated a protection ≥50% against EIB in the majority of children (aged 5-16) 4 h after a single low dose of ICS (44).…”
Section: Maintenance Medicationmentioning
confidence: 99%
“…Besides these chronic effects, previous studies have also shown acute protection against EIB after administration of only a single dose of ICS ( 43 46 ). Visser et al demonstrated a protection ≥50% against EIB in the majority of children (aged 5–16) 4 h after a single low dose of ICS ( 44 ). In adult asthmatics, acute positive effects on lung function of a single high dose ICS have been shown to last for at least 8 to 9 h ( 47 ).…”
Section: Asthma Medication and Eibmentioning
confidence: 99%